Hormesis and Adaptive Cellular Control Systems - Qiang Zhang; Jingbo Pi; Courtney G. Woods; Annie M. Jarabek; Harvey J. Clewell; Melvin E. Andersen (SAGE Publishing, 2008)
Hormetic dose response occurs for many endpoints associated with exposures of biological organisms to environmental stressors. Cell-based U- or inverted U-shaped responses may derive from common processes involved in activation of adaptive responses required to protect cells from stressful environments. These adaptive pathways extend the region of cellular homeostasis and are protective against ultimate cell, organ, and system toxicity. However, the activation of stress responses carries a significant energetic cost to the cell, leading to alterations of a variety of basal cellular functions in adapted or stressed cells. This tradeoff of resources between the unstressed and adapted states may lead to U-or inverted U-shaped dose response curves for some precursor endpoints. We examine this general hypothesis with chlorine, a prototype oxidative stressor, using a combination of cellular studies with gene expression analysis of response pathways and with computational modeling of activation of control networks. Discrete cellular states are expected as a function of exposure concentration and duration. These cellular states include normal functioning state, adaptive and stressed states at mild to intermediate exposures, and overt toxicity in the presence of an overwhelming concentration of stressors. These transitions can be used to refine default risk assessment practices that do not currently accommodate adaptive responses.